Analytical and experimental study of the electric shielding effectiveness of a metallic enclosure for off-centred apertures - Ahmad Po'ad, Farhana (2007)
An electromagnetic shielding is frequently used to protect against external fields and leakage from electronic products to meet the electromagnetic compatibility (EMC) requirement. However, it is a great challenge to design a practical electromagnetic shield because its integrity is often compromised by apertures and slots used to accommodate ventilation or access to interior components. Such openings allow exterior fields to be coupled onto printed circuit boards (PCBs), thus inducing current and voltage on interior conductors. This phenomenon will degrade the shielding effectiveness (SE) of the enclosure. This research is performed to investigate the effects of apertures on the SE of a rectangular metallic enclosure for off-centred apertures by using an analytical formulation and experimental study. The theories developed by other researchers have been extended to take into account the contribution of higher order modes and off-centred apertures in the enclosure. The electric shielding effectiveness, Se were calculated as a function of frequency, enclosure dimensions, aperture dimensions, aperture locations and various observation points by employing a transmission line equivalent circuit approach. The extended formulation applies only to rectangular enclosures with rectangular apertures, but simple modifications were included to account for square, circular, multiple apertures and the effect of the enclosure contents. Generally, the analytical results of the Se are in good agreement with measurement results which were conducted in a Gigahertz Transverse Electromagnetic (GTEM) cell in the range of frequency from 10 MHz to 1 GHz. As an example, the Se at 600 MHz using analytical formulation has 92% similarity compared to measurement results. It was also found out that by taking into account five modes above the TEio will contribute an additional 35 dB to the Se at 800 MHz. This indicates the significance of multimode in determining Se for enclosure with off-centred aperture. In addition, the results agree with present understanding on the dependence of SE on aperture sizes, aperture shapes, aperture locations and effect of electromagnetic losses in the enclosure. The reduction of Se by about 9.5 dB due to multiple apertures indicated by 20 log n where n is the number of apertures was also successfully endorsed in this work. The findings generated from this research work can be used as design rules by designers of practical shielded enclosures. Future works can be carried out to incorporate enclosures of various shapes and sizes at frequencies greater than 1 GHz.